The Relationship Between the Acquisition of Language Patterns and Oral Expression Skills Among Students with Learning Difficulties in the English Language During the Covid-19 Pandemic - Mohamad Ahmad Saleem Khasawneh (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2021)
This study aimed at identifying the relationship between the acquisition of language patterns and oral expression skills among students with learning difficulties in the English language during the Covid-19 pandemic. The study used the experimental approach and implemented the program on a sample of 84 students divided into an experimental group (n = 42) and a control group ( n = 42). The instruments of the study consisted of the training program, a test of language patterns, and a test for the evaluation of oral expressive performance. The study found the existence of a statistically significant relationship between the acquisition of language patterns and oral expression skills among students with learning difficulties in the English language.